Catch composition, diversity and temporal changes in trawl net fishery in inshore waters of Bintulu Coast, Sarawak, Malaysia - Kumar, Uttam (2019)
Declining diversity is a common problem in many habitat especially in inshore waters. Past researches reported that trawl fisheries has been damaging inshore ecosystem over the last few decades. Trawl net is the most common fishing gear operating in Sarawak as well as Malaysian inshore waters. Few studies on fish composition, population dynamics has been done in coastal waters of Bintulu, Sarawak. Despite it has significant contribution to the Bintulu fisheries economy, the studies on the composition and diversity of trawl net fishery is poorly understood. Therefore, temporal changes in diversity and composition of the fisheries assemblages in association with ecological factors in Bintulu inshore waters were examined on collected data from trawl net fishing over four seasons of Southwest monsoon (SWM), Inter-monsoon October (IMO), Northeast monsoon (NEM) and Inter-monsoon April (IMA) of 2016-2017. Furthermore, length-weight relationships of most abundant and unreported species caught by trawl net were analyzed. A total of 63 species belonging to 40 families were identified where, 11 species found omnipresent. Species diversity was recorded higher (H´=2.61) in NEM and lower (H´=0.51) in IMA. Among the species Kurtus indicus was the highest abundant (58% of the total catch) followed by Photopectoralis bindus (15%), and Opisthopterus tardoore (7%). Fish abundance showed significant temporal changes but species diversity, plankton abundance were not significant with temporal difference. Temperature, salinity, pH, dissolved oxygen (DO) and rainfall showed classical temporal difference (P<0.05). No significant temporal difference was found on chlorophyll a and water nutrients. Canonical Correspondence Analysis (CCA) indicated that dissolved oxygen, total suspended solid (TSS), rainfall and salinity were the most important ecological factors affecting fish assemblage structure. Relation of ecological parameters with individual species (Spearman rank) like Secutor interruptus were significantly correlated with DO (P<0.001; r2=0.898). In terms of temporal impact on parameters (Rank Analysis-Wilcoxon), SWM showed parallel similarity with environmental parameters and fish abundance. The highest abundant Kurtus indicus showed significant positive correlation with TSS, salinity and conductivity and negative correlation with temperature (P<0.05; r2=-0.618). Comparing to existing database, 84% from captured species has commercial value and among those 38% were encountered in trawl net as juvenile. Among the analyzed species, Nibea semifasciata, Filimanus similis, Opisthopterus tardoore and K. indicus showed positive allometric growth (b=3), which indicates the food availability and the overall supportive environment were good for those species. Fish composition and diversity in the inshore waters of Bintulu discovered immensely rich and highly related to eco-biological factors in this study. The findings of this study would help to understand the inshore fishery resources, status and its ecosystem profile which will help to manage this fishery resource of Bintulu as well as Sarawak, South China Sea region in future.